Pentateuchal traditions in the late second Temple Period proceedings of the International Workshop in Tokyo, August 28-31, 2007 - Moriya, Akio.; Hata, Gōhei, 1942- (Leiden : BRILL, 2012)
This volume consists of collected essays, which was first read at the International Workshop on the Study of the Pentateuch with Special Emphasis on Textual Transmission History in the Hellenistic and Roman Periods held August 28-31, 2007 in Tokyo.
A.Y. Collins. The Reception of the Torah in Mark: The Question about the Greatest CommandmentH. W. Attridge. Creation and Sacred Space: The Reuse of Key Pentateuchal Themes by Philo, the Fourth Evangelist, and the Epistle to the Hebrews; SPECIAL CONTRIBUTION; Y. Ikeda. A Geographical Horizon in the Textual Transmission of Pentateuch -- Searching for Further Points of Contact between East and West; Index of Modern Authors; Index of Ancient Sources.
Description based on print version record.
Keywords: Bible. -- History -- Congresses; Bible. -- Criticism, interpretation, etc. -- Congresses; Judaism -- History -- Post-exilic period, 586 B.C.-210 A.D. -- Congresses; Dead Sea scrolls -- Relation to the Old Testament -- Congresses; Bible. -- Relation to the Old Testament -- Congresses; RELIGION / Biblical Studies / Old Testament; Electronic books